Authentication of the green monkey kidney Vero76 cell lines subcultured through many generations - Lien, Nguyen Thi Kim; Van Tung, Nguyen; Huy Hoang, Nguyen; Thi Mai Huong, Nguyen; Thi Van Quynh, Nguyen; Van Hung, Pham (Vietnam Journal of Biotechnology, 2020)
The Vero76 cell lines isolated from the kidney of an African green monkey (Chlorocebus aethiops sabaeus), are commonly used for viral culture, vaccine development, and cytotoxicity assays. However, subculturation of cell lines over multiple generations can lead to a genetic change in these cell lines compared to the original cell. This will lead to deviations in results of research that using the modified cell lines. Therefore, identification and evaluation periodically the genetic stability of cell lines after subculture are necessary. In recently studies, cell authentication by using STR markers (short tandem repeat markers) have been becoming a simple and effective method that used commonly. In this study, we used eight STR markers: D17S1304, D5S1467, D19S245, D1S518, D8S1106, D4S2408, D6S1017, and DYS389 for cell lines authentication and evaluation of the genetic stability of subcultured Vero76 cell lines. The STR indicators were amplified, sequenced and compared with the original cell to identify the differences between cell lines in subcultured generations. The evaluation results showed that these cell lines did not have any differ compared with the original cell line, this confirmed that the genetic of the cell lines were stability. The results also suggested that STR markers can be used to authenticate for Vero76 cell lines.